Odpowiedzi

2009-11-25T20:05:41+01:00
1.Zredukuj wyrazy podobne:
a)-4x-7-3x+7=-7x
b)x-2xy+½x-1/3x-1/3xy=x+3/6x-2/6x-2 1/3xy=7/6x-2 1/3xy
c)-x²+y²-2x²-2y²=-3x²-y²
d)-x²+2x-3x+x²=-x
e)4x+4-7x-½=-3x+3½
f)-2ab+12a-4ab-16a=-6ab-4a
2009-11-25T20:06:32+01:00
A)-4x-7-3x+7= -7x
b)x-2xy+½x-1/3x-1/3xy= x - 2xy + 3/6x - 2/6x - 1/3xy = 1 i 1/6x -2 i 1/3 xy
c)-x²+y²-2x²-2y² = -3x² - y²
d)-x²+2x-3x+x²= -x
e)4x+4-7x-½= 3 i 1/2 - 3x
f)-2ab+12a-4ab-16a= - 6ab - 4a
2009-11-25T20:10:49+01:00
A) = - 7x
b) = 1 1/6 x - 2 1/3 xy
c) = - 3x² - y²
d) = -x
e) = -3x+ 3 1/2
f) = -6ab-4a